Crop rotation and fungicides impact microbial biomass, diversity and enzyme activities in the wheat rhizosphere - Lupwayi, Newton Z.; Turkington, T. Kelly; Tidemann, Breanne D.; Kubota, Hiroshi; Polo, Rodrigo O. (Frontiers in Agronomy, 2024)
Sustainable crop production systems should promote large and diverse soil microbial communities to enhance biological soil processes rather than depend solely on chemical interventions that include pesticide applications. Crop rotation increases above-ground temporal diversity which, relative to monoculture, usually increases soil microbial diversity. But comparisons between short and long crop rotations that also include pesticide effects are rare. A 5-yr (2013-2017) field study was conducted to investigate crop rotation and fungicide effects on the soil microbiome and activity. There were nine rotations, with or without fungicide applications, that included four 2-yr rotations (wheat preceded by canola, barley, pea, or flax), four 3-yr rotations where barley or canola were added to the 2-yr rotations, and one rotation where canola and wheat were stacked (canola-canola-wheat-wheat). In 2017, soil microbial biomass, composition, diversity and enzyme activities were measured in the rhizosphere of the final wheat crop in each rotation. Fungicides reduced fungal richness (the number of different fungal taxa) in the wheat rhizosphere (e.g., Chao1 indices of 64.0 vs. 79.9) especially in 2-yr rotations, but rotation length/type and the crops that preceded wheat had different effects on different taxa. Two of the three most predominant prokaryotic phyla, Proteobacteriota and Actinobacteriota, responded differently to rotation length: 3-yr rotations enriched the former (27.4% vs. 20.1% relative abundances), but 2-yr rotations enriched the latter (19.9% vs. 28.3% relative abundances). Relative to oilseed crops preceding the sampled wheat, a field pea preceding crop enriched Actinobacteriota (31.7% vs. 24.8% relative abundances) and the most abundant fungal class, Sordariomycetes (39.1% vs. 22.1% relative abundances), in addition to increasing microbial biomass carbon (MBC) and arylsulphatase activity by 33% and 57%, respectively. Correlations of the relative abundances of fungal or prokaryotic genera with β-glucosidase and arylsulphatase activities were similar (both positive or negative), but they were the opposite of correlations with acid phosphomonoesterase, suggesting a close link between C and S cycling. Besides the nutrient cycling implications of these soil microbial characteristics, there is need to study their biological disease control significance.